The two fundamental problems of ethics - Schopenhauer, Arthur (Oxford world's classics (Oxford University Press), 2010)
Schopenhauer argues, in uniquely powerful prose, that self-consciousness gives the illusion of freedom and that human actions are determined, but that we rightly feel guilt because our actions issue from our essential individual character. He locates moral value in the virtues of loving kindness and voluntary justice that spring from the fundamental incentive of compassion. Morality's basis is ultimately metaphysical, resting on an intuitive identification of the self with all other striving and suffering beings. The Introduction by leading Schopenhauer scholar Christopher Janaway gives a clear summary of the argument of the essays in the context of Schopenhauer's life and works and the history of ethics in the modern period. --from publisher description